Acoustic Pronunciation Variations Modeling for Standard Malay Speech Recognition - Seman, Noraini; Jusoff, Kamaruzaman (2008)
This paper presents different methods of handling pronunciation variations in Standard Malay (SM) speech recognition. Pronunciation variation can be handled by explicitly modifying the knowledge sources or improving the decoding method. Two types of pronunciation variations are defined, namely, complete or phone changes and partial or sound changes. Complete or phone change means that one phoneme is realized as another phoneme. Meanwhile, a partial or sound change happens when the acoustic realization is ambiguous between two phonemes. Complete or phone changes can be handled by constructing a pronunciation variation dictionary to include alternative pronunciations at the lexical level or dynamically expanding the search space to include those pronunciation variants. Sound or partial changes can be handled by adjusting the acoustic models through sharing or adaptation of the Gaussian mixture components. Experimental results show that the use of a pronunciation variation dictionary and the method of dynamic search space expansion can improve speech recognition performance substantially. The methods of acoustic model refinement were found to be relatively less effective in our experiments.